0638 Circadian rhythms among youth with craniopharyngioma. (25th May 2022) - Kamara, Dana; Crabtree, Valerie McLaughlin; Crowley, Stephanie; Hancock, Donna; Semko, Joshua; Merchant, Thomas; Mandrell, Belinda
Abstract: Introduction: Craniopharyngioma is an intracranial tumor located in the hypothalamic and pituitary region. Despite high survival rates for youth with craniopharyngioma, quality of life is substantially affected. Morbidity includes high rates of sleep disruption, particularly disorders of hypersomnolence. Circadian rhythms may also be affected due to the proximity of the tumor and subsequent treatment to the hypothalamic-pituitary-adrenal axis, though the role of circadian rhythms has been less studied in this patient population. To evaluate circadian rhythms among youth with craniopharyngioma, dim light melatonin onset (DLMO), an established marker of the circadian system, was estimated. Methods: Fifty-five patients between the ages of 7 and 20 years participated in this study. Data were collected prior to completion of proton therapy (if indicated). Participants provided hourly saliva samples, in their homes, starting 3 hours prior to habitual bedtime until 1 hour following in dim light conditions (<30 lux). DLMO was calculated based on a threshold of 4 pg/ml. Participants also wore actigraphs to measure sleep patterns. We derived bedtime and waketime from actigraphy and calculated phase angles to bedtime and waketime. DLMO timing and phase angles were compared to published norms for healthy youth ages 9 to 17 years. Results: DLMO could not be estimated for almost half of the sample (n=25), most often due to a melatonin value above the threshold at the first collection time point. Higher grade of hypothalamic involvement and the presence of diabetes insipidus predicted inability to capture DLMO. Subsample analyses of participants with DLMO (n=30) showed later DLMO timing and shorter phase interval to bedtime than the healthy reference sample. Conclusion: With standard practice for DLMO estimation, we only obtained estimates for slightly more than half our sample. This may reflect circadian rhythm disturbances or advanced circadian phase. Relative to published norms, those with captured DLMO had later DLMO timing and shorter phase angles to bedtime, indicating sleep at an earlier circadian phase. These findings suggest possible circadian rhythm disruption in pediatric craniopharyngioma. Methodological differences among samples may also contribute to findings. Further examination of circadian rhythm disruption and relations with other sleep disturbances is needed. Support (If Any): This work was supported by the Cancer Center Support Grant (CA21765) from the National Cancer Institute and ALSAC.